THE EFFECT OF COMBINATION MENIRAN ROOT (Phylanthus niruri L.) AND JAVA ACID LEAVES (Tamarindus indica L.) on ALOKSAN-INDUCED DARNESS GLUCOSA RATS (Rattus norvegicus) - Asri SR, Muhammad; Gisela; Muzayyidah (Journal of Pharmaceutical Science and Herbal Technology, 2024)
Meniran root (Phylanthus niruri L.) and tamarind (Tamarindus indica L.) have flavonoid compounds that function to repair pancreatic tissue damage caused by DNA alkyl groups from alloxan induction. This study aims to determine the activity of a combination of meniran root extract (Phylanthus niruri L.) and tamarind leaves (Tamarindus indica L.) on blood glucose levels of male rats (Rattus norvegicus) induced by alloxan. This study was carried out experimentally. White rats up to 15 heads were divided into 5 groups. Alloxan induction at a dose of 125 mg/kgBB intraperitoneally to cause pancreatic damage was performed in 5 treatment groups. Three treatment groups were treated with different doses of a combination of meniran and tamarind root extracts, (P1) 7.5 mg/KgBB, (P2) 10 mg/KgBB and (P3) 15 mg/KgBB, one group as negative control (K-) was given 1% Na CMC and positive control (K+) was given 5 mg glibenclamide. The combination of meniran root extract (Phylanthus niruri L.) and tamarind leaf (Tamarindus indica L.) was given for 1 day. Glucose levels were checked after 2 hours, 4 hours, 6 hours and 24 hours of administration. The results showed that the three concentrations of a combination of meniran root extract (Phylanthus niruri L.) and tamarind leaf (Tamarindus indica L.) can reduce the blood glucose levels of male rats (Rattus norvegicus) induced by alloxan.